Is a single calibration for the TloadDback cognitive fatigue induction task reliable? - Jeromy Michael Hrabovecky; Jeromy Michael Hrabovecky; Xavier De Tiège; Xavier De Tiège; Chloé Samyn; Guillermo Borragán; Philippe Peigneux; Mélanie Strauss; Hichem Slama; Hichem Slama (Frontiers in Psychology, 2025)
TloadDback task was introduced as a novel task for inducing cognitive fatigue by accounting for the cognitive capacity of each individual's processing time needs stimulus time duration (STD). The task is carried out on different days with calibration occurring on 1 day and fatigue induction occurring on another. The aim of this within subjects study is to assess the reliabilityThe of a single calibration. Fifty-one healthy participants (age = 32.2 +/– 13.45; sex F = 41) completed the TloadDback calibration phase on three different days at three different moments of the day (counterbalanced for morning, afternoon, and evening). Sleep quality, state fatigue and state sleepiness were considered as control variables. Comparisons across the 3 calibration sessions (χ2(2) = 34.1, p < 0.0001) showed a significant STD decrease (i.e., performance improvement) with the most salient between sessions 1 and 2 (t = 3.98, p = 0.0003***). However, the improvement occurred for only 2/3 of participants. STDs from the 3 calibrations were significantly correlated (α = 0.78). Differences in sleep quality, state fatigue and state sleepiness did not correlate with STD changes. Results indicate that a single calibration may not put all participants in their maximal cognitive load condition and that a second calibration could be more appropriate. Nonetheless, the fact that the 3 calibrations were significantly correlated and that 1/3 of participants did not vary between sessions 1 and 2 suggest that the measure is rather reliable and that a single calibration can be sufficient for placing participants in a close to maximal cognitive load condition for cognitive fatigue induction if a second calibration is not possible.